Accountability for sustainability: an approach beyond the accounting mainstream - Soares, Eduardo Codevilla (2022)
This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001